2018
DOI: 10.1016/j.pragma.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Using context and prosody in irony understanding: Variability amongst individuals

Abstract: The present study sought to investigate, in French, the relative influence of both contextual incongruity and prosodic cues on irony comprehension and to explore whether individual differences exist regarding the relative influence of these markers of irony. Ninety-five participants, all native French speakers, were included in the study. They listened to a context followed by a target utterance presented with either an ironic prosody or a neutral prosody and then, they had to decide whether this target uttera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Assuming the hearer's perspective, the most powerful cue to detect the speaker's ironic intent is the incongruence between the context and the statement (see, a.o., Rivière et al, 2018), even if ironic compliments might require the presence of an explicit statement to be correctly perceived. To avoid misunderstandings, the ironic speaker can (but does not need to) also display the so-called ironic markers, that is, meta-communicative cues that alert the audience that his or her comment should not be interpreted literally.…”
Section: Verbal Ironymentioning
confidence: 99%
“…Assuming the hearer's perspective, the most powerful cue to detect the speaker's ironic intent is the incongruence between the context and the statement (see, a.o., Rivière et al, 2018), even if ironic compliments might require the presence of an explicit statement to be correctly perceived. To avoid misunderstandings, the ironic speaker can (but does not need to) also display the so-called ironic markers, that is, meta-communicative cues that alert the audience that his or her comment should not be interpreted literally.…”
Section: Verbal Ironymentioning
confidence: 99%
“…Understanding irony requires the integration of different types of contextual information. The perception of an incongruity between the context and the target statement is known to be an essential condition for understanding irony (Ivanko & Pexman, 2003; Kreuz & Glucksberg, 1989; Rivière, Klein, & Champagne-Lavau, 2018). Other markers, although not necessary, may also help (Attardo, 2000).…”
mentioning
confidence: 99%
“…Moreover, Colston (2000) and Kumon-Nakamura et al, (1995) observed that when stories contain an allusion to a failed expectancy, positive evaluation (e.g., "this is great") of a negative outcome and negative evaluation (e.g., "this sucks") of a positive outcome were judged as more ironic than their literal counterparts. Other studies have shown that a larger contrast between expectations and reality increases the recognition of sarcasm and irony (Champagne-Lavau, Charest, et al, 2012;Champagne-Lavau, Cordonier, Bellmann, & Fossard, 2018;Deliens et al, 2018;Gerrig & Goldvarg, 2000;Ivanko & Pexman, 2003;Rivière, Klein, & Champagne-Lavau, 2018;Voyer et al, 2014;Woodland & Voyer, 2011) while the absence of incongruity between expectation and reality leads to interpreting the target utterance as sincere.…”
Section: Introductionmentioning
confidence: 98%